Quantitative evaluation of impact cracks near the borehole based on 2D image analysis and fractal theory. (March 2022) - Li, Yanliang; Peng, Jianming; Zhang, Ling; Zhou, Jian; Huang, Chaoyang; Lian, Moke
Highlights: The feasibility of using fractal dimension theory to analyze impact cracks is studied. The impact crack patterns are classified and explained systematically. The distribution area of the impact cracks near the borehole is divided, and the evolution law of the impact cracks is revealed. The function relation between fractal dimension of impact cracks and surface crack porosity is given. Abstract: Impact cracks near the borehole are beneficial to geothermal energy development in many aspects, such as hydraulic fracturing, perforation and so on. However, the quantitative evaluation of the impact cracks near the borehole has not been studied. In the present paper, the fractal dimension of the impact crack has been calculated by the box-counting method to capture the complexity and irregularity of the impact crack pattern. The results show that the impact crack has fractal characteristics, which proves that it is feasible to use the fractal dimension method to quantitatively evaluate the impact cracks. The fractal dimension of the impact cracks is between 1.27 and 1.64. Moreover, the variation of fractal dimension with the increase of the dimensionless distance shows a remarkable regionalization. Simultaneously, the impact crack patterns are classified and divided into seven kinds according to their shape characteristics, and T-shaped, Y-shaped, and wave-shaped cracks are the main kinds of impact cracks. Finally, the surface crack porosity parameter is introduced to characterize the actual content of impact cracks, and the maximum surface crack porosity is 15.9%. Through the comprehensive evaluation of fractal dimension and surface crack porosity, it can be estimated that the influence of percussion drilling on rocks near the borehole ranges from about 1.5 times to 1.7 times the diameter of the borehole. The concept of fractal dimension provides a new perspective for a quantitative understanding of impact cracks, and the presented experimental results can be a useful reference for building numerical models.